Intestinal obstruction mimicking intra-abdominal hemorrhage in a teenager with familial thrombocytopenia: a case report - Sutaryo Sutaryo; Kaiser Ali; Untung Widodo; Nunik Agustriyani; Edy Moeljono; Mark Belletrutti (Paediatrica Indonesiana, 2003)
Inherited bleeding disorders are a heterogeneousgroup of disease that is complicated byhemorrhagic episodes, spontaneous, and post-traumatic. Included in this category of conditionsare Familial Thrombocytopenias (FT). FT are aheterogeneous group of inherited disorders that varyin severity with regard to the degree of reduction inplatelet counts and in expression of bleedingmanifestations. As in acquired thrombocytopenias, FTpatients are at risk for hemorrhagic complications.Rarely, patients with inherited non-thrombocytopeniableeding disorders can develop complications of acuteabdomen 1,2 which present as intraabdominalhemorrhage. We report a case of intestinal obstructionmimicking an uncomplicated intraabdominalhemorrhage in a teenager with FT.